Pemberdayaan Masyarakat Muda Sekolah Melalui Upaya Penerapan Mitigasi dan Tanggap Darurat Bencana - Esi Afriyanti; Nofrizon Nofrizon; Rika Fatmadona; Emil Huriani; Fitri Mailani; Boby Febri Krisdianto; Rahmi Muthia; Devia Putri Lenggogeni; Leni Merdawati (Warta Pengabdian Andalas, 2019)
The city of Padang has a topography prone to flooding or inundation and other natural disasters such as earthquakes accompanied by tsunamis. The city of Padang, in the collision of the Indian Ocean Plate and the Australian Plate which infiltrated under the Eurasian Plate, formed the Benioff Zone, an earthquake zone with seismicity magnitude greater than 5 on the Richter scale. With the condition of the city of Padang which is prone to disasters, it is very necessary for community participation, especially in the prevention of the stages of the pre-disaster (disaster mitigation), during the emergency response, and post-disaster because the people who deal directly with the disaster. Schools play an important role and have several functions in disaster risk reduction including facilitating and cooperating with the surrounding environment, improving community skills, refugee centers when disaster strikes. Therefore it is necessary to conduct activities that can improve the understanding and skills of young school communities, especially students in disaster mitigation and disaster response. This activity was carried out on November 2, 2019 at SMAN 9 Padang with 42 participants. The method used in this activity is counseling about disasters, the concept of triage. Demonstrations are carried out to improve students' skills in learning. The results of the activity found that there was an increase in student knowledge after being given health education and increasing students' abilities in triage and education. Furthermore, teachers and students are provided with booklets and leaflets which are a means to increase knowledge about disaster mitigation and response. In the future, training is needed continuously about disaster mitigation and emergency response so that students are trained when disasters occur.